Analisis Penduduk dan Dampaknya terhadap Pertumbuhan Ekonomi Kota Tual 2012 – 2024 - Hasni Zubaidah Tamher; Teddy Ch. Leasiwal; Andre Sapthu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effects of population growth, the labor force participation rate, and the level of urbanization on economic development in Tual City during the 2012–2024 period. A quantitative approach using multiple linear regression (Ordinary Least Squares/OLS) was employed to examine the relationships among the variables. The dependent variable was economic development, measured by real Gross Regional Domestic Product (GRDP) per capita, while the independent variables consisted of population growth, the labor force participation rate, and the level of urbanization. Secondary data were obtained from official publications issued by Statistics Indonesia (BPS) for Tual City and Maluku Province throughout the observation period. The results indicate that the labor force participation rate and urbanization have positive and significant effects on economic development, whereas population growth has a negative but statistically insignificant effect. These findings suggest that improvements in labor productivity and the concentration of the population in urban areas play a greater role in promoting regional economic growth than overall population growth. Therefore, development policies in Tual City should focus on improving the quality of human resources, strengthening productive sectors, and promoting balanced development across areas to transform demographic potential into sustainable economic strength.